Change in cannabis use, clinical symptoms and social functioning among patients with first-episode psychosis: a 5-year follow-up study of patients in the OPUS trial. Issue 1 (January 2014) - Clausen, L.; Hjorthøj, C. R.; Thorup, A.; Jeppesen, P.; Petersen, L.; Bertelsen, M.; Nordentoft, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Several studies indicate that cannabis use among patients with psychotic disorders is associated with worse outcome, but only a few studies have controlled for baseline condition and medication. Method At 5-year follow-up, interviews were carried out with 314 first-episode psychosis patients included in the OPUS trial. The patients included were in the age range of 18 to 45 years old and 59% were male. Cannabis use was extracted from the Schedule for Clinical Assessment in Neuropsychiatry. At follow-up, the patients were divided into different groups according to the variable cannabis use: abstainers, stoppers, starters and continuers. Psychotic, negative and disorganized dimensions (ranging from zero to five) were calculated for each of the four groups based on the Schedule for the Assessment of Positive and Negative Symptoms in Schizophrenia. Results Cannabis users were younger (24.6 years v. 27.4 years, p < 0.001) and had a lower level of education. At the 5-year follow-up, users of cannabis had higher scores on the psychotic dimension [difference 0.97, 95% confidence interval (CI) 0.41–1.53, p = 0.001] and lower levels of the Global Assessment of Functioning (difference 8.26, 95% CI 2.13–14.39, p = 0.01). Those who stopped using cannabis between entry and 5-year follow-up had a significantly lower level of psychotic symptoms at 5-year follow-up even after controlling for baseline level of psychotic symptoms and for insufficient antipsychotic medication (adjusted difference in psychotic dimension –1.04, 95% CI –1.77 to –0.31, p = 0.006). Conclusions Continuous cannabis use was associated with higher levels of psychotic symptoms after 5 years, and this association was only partly explained by insufficient antipsychotic medication.